Exploring regional coastal sediment pathways using a coupled tide-wave-sediment dynamics model. (15th January 2023) - Davies, A.G.; Robins, P.E.; Austin, M.; Walker-Springett, G.
Abstract: Knowledge of sediment transport pathways is important for coastal management as well as for offshore infrastructure such as wind farms and other renewable energy installations. Here a three-way coupled model of tides, waves and sediment dynamics is presented, which extends the approach of Davies and Robins (2017) for the prediction of the locally-varying seabed roughness ks resulting from the interaction between the flow (tides and waves) and the bed sediment (grain size mixture) subject to wave-current interaction (WCI) at the seabed. The model was applied to the North Wales coastal area, with particular emphasis on an extensive shore-connected sand bank (Constable Bank), the stability of which was investigated through the study of residual sediment circulation patterns. Multi-beam (MBES) and seabed rig (AWAC) observations have allowed validation of the predicted ks and hydrodynamics, respectively. With due allowance for the supply of mobile sediment, the agreement between predicted ks and observed bedform height was generally good. The model has been used to determine residual velocities and sediment pathways, both with and without wave effects included. Wave influence and WCI are predominant in nearshore areas, affecting the magnitude and direction of the residual fluxes. A key modelling outcome offshore is a clockwise residual circulation pattern for water and sediment around the end of Constable Bank, set within a generally eastward net drift of sediment in the wider study area. Highlights: Sediment pathways predicted using a novel 3-way-coupled tide-wave-sediment model. Coastal area flow modelled with temporally/spatially varying bed roughness. Implementation in Telemac of wave-current interaction at the seabed. Comparison between MBES-observed and Telemac-predicted physical bed roughness. Residual flow and transport predicted highlighting a shore-connected sandbank.